Our journey with an AI assistant offering narrative therapy on WhatsApp. - Chan, Chitat; Zhao, Jiahui; Zhao, Yunmeng (Journal of Social Work Practice, 2025)
This study examines the integration of AI chatbots into social work, with a focus on democratising AI for use in Narrative Therapy (NT). As AI becomes more accessible, social work encounters new opportunities to utilise these tools in practice, but also faces significant challenges. The study explores the feasibility of using customisable GPT platforms to develop an AI chatbot for NT sessions and assesses its performance. An autoethnographic case study was conducted using a chatbot configured with the OpenAI Assistant API to perform NT on WhatsApp. Findings suggest that while practitioners can configure the chatbot to guide users through NT stages and adapt to interactions, there are still limitations, such as the need for basic coding and technical knowledge for deployment and enhancement. The study highlights both the potential and the challenges of AI in social work, advocating for enhanced training, interdisciplinary collaboration, and the cautious development of AI-assisted practices.